Influence of multimorbidity on the risk of events in men with chronic coronary artery disease after myocardial infarction and percutaneous coronary intervention - D. V. Dedov; V. P. Mazaev; A. N. Kovalchuk; A. A. Komkov; S. V. Ryazanova (Кардиоваскулярная терапия и профилактика)
Aim. To study the effect of multimorbidity on the risk of cardiovascular events (CVEs) in men with chronic coronary artery disease (CAD) after myocardial infarction (MI) and percutaneous coronary intervention (PCI).Material and methods. A total of 101 men with chronic CAD after MI and PCI were included in the study (mean age 60,5±6,1 years). Of these, taking into account the non-inclusion criteria and consent to examination, 2 following groups were formed: first (n=39) — men without CVEs; 2nd (n=39) — men with CVEs. In both groups, we studied the detection rate of grade I hypertension (HTN), class I obesity, hypercholesterolemia (HCE), and type 2 diabetes (T2D). The influence of HTN, obesity, HCE, and T2D on the risk of cardiovascular events was analyzed based on the calculation of contingency tables and Pearson's χ2, as well as odds ratios (OR) with 95,0% confidence intervals (CI). The follow-up period for patients averaged 3,6±0,5 years.Results. In men of group 2, compared with group 1 patients, grade I HTN, class I obesity, HCE were diagnosed more often in 1,3 (p=0,044), 1,4 (p=0,047), 1,2 (p=0,059) times, respectively. An increase in the risk of CVEs in men with chronic CAD, who underwent MI and PCI was associated with the detection of grade I HTN, class I obesity, HCE — OR 2,44 (CI: 1,88-6,75), OR 1,78 (CI: 1,56-4,62), OR 1,37 (CI: 1,11-4,17), respectively.Conclusion. Thus, the detection rate of grade I HTN, class I obesity and HCE in men with chronic CAD and CVEs at long-term follow-up after MI and PCI was significantly higher compared to patients with chronic CAD without CVEs after PCI. At the same time, the detection of grade I HTN, class I obesity and HCE were associated with an increased risk of cardiovascular events.